Efek Antifeedant Umpan Blok Singkong (Manihot esculenta) terhadap Perubahan Bobot Badan Tikus Putih (Mus musculus L.) - Lia Wulandari; Dwi Sutiningsih; Martini Martini (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2019)
Background: Rodent-borne disease control relies on reservoir control is rodent animals. Controlling techniques are urgent to do, such as biopesticide use. The use of biopesticide should be developed to reduce the negative impact of chemical rodenticides. Manihot esculenta have cyanogenic glycosides with antifeedant effects. The potential of biopesticide used for pest management.Methods: Block bait consumption of cassava (Manihot esculenta) on body weight of Mus musculus L. was carried out an experimental rat. The objective of the test was to observe the direct effect of cassava block bait on mice. The animal model was divided into six treatment groups (5.75%; 11.5%; 23%; 46%; 92%; 184%) with control. Each treatment group was repeated 5 times. Treatment was given during the 14 days orally. The parameters that were obtained are feed consumption and body weight.Result: This experiment showed that there was a difference in feed consumption and on body weight mice in all animal model groups.Conclusion: It concluded that block bait of cassava (Manihot esculenta) in different concentrations has an antifeedant effect, causing alteration on feed consumed and body weight of Mus musculus L.